Antioxidant and Cytotoxic Activity of Different Extracts of Zanthoxylum Alatum - Karmakar, Indrajit; Haldar, Sagnik; Chakraborty, Mainak; Dewanjee, Saikat; Haldar, Pallab Kanti (Free Radicals and Antioxidants)
Objectives: The present study evaluates the antioxidant and cytotoxic activity of different extract (methanol, chloroform, petroleum ether) of Zanthoxylum alatum. Methodology: The antioxidant activities of all the three above mentioned extracts of Zanthoxylum alatum were measured by different in vitro standard methods like 1,1-diphenyl-2-picrylhydrazil radical (DPPH), superoxide anions, nitric oxide, hydroxyl radicals and reductive assay. On the basis of antioxidant properties total phenolic, total flavonoid, CCl4 -induced in vivo antioxidant and in vitro cytotoxicity were measured for methanol extract of Zanthoxylum alatum (MEZA). Cytotoxicity was determined in Ehrlich Ascites Cancer (EAC) cells by trypan blue exclusion method. Results: The extracts exhibited antioxidant activities in a dose dependent manner. The IC50 values of Methanol, Chloroform, Petroleum ether extracts and standard for DPPH are 3.63 ± 0.14 μg/mL, 9.33 ± 0.42 μg/mL, 7.70 ± 0.31 μg/mL and 7.87 ± 0.39 μg/mL; for Superoxide are 19.80 ± 0.96 μg/mL, 129.70 ± 2.57 μg/mL, 168.10 ± 2.26 μg/mL and 11.76 ± 0.72 μg/mL; for Nitric oxide are 105.0 ± 1.64 μg/mL, 157.60 ± 1.99 μg/mL, 185.30 ± 2.48 μg/mL and 28.48 ± 1.06 μg/mL; for Hydroxyl radical are 28.10 ± 0.75 μg/mL, 81.50 ± 1.88 μg/mL, 72.47 ± 1.76 μg/mL and 12.24 ± 0.82 μg/mL. Reductive ability of the extracts was also tested where dose dependent reducing capability was observed. In case of in vivo antioxidant lipid peroxidation, reduced glutathione, superoxide dismutase and catalase parameters significantly change towards the normal levels. MEZA showed satisfactory phenolic and flavonoid content which support the cytotoxicity with IC50 value 102.30 ± 0.81 μg/mL. Conclusion: The study showed that among all the three extract MEZA has better dose dependant antioxidant and cytotoxic activity. Further research is going on to find out the active principle(s) of MEZA for its cytotoxic activity.
Keywords: Antioxidant; Cytotoxicity; Ehrlich Ascites Cancer; Flavonoid; Zanthoxylum alatum